2021
DOI: 10.3389/frwa.2021.626849
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Sequencing and Quantitative Real-Time PCR for Fecal Pollution Assessment in an Urban Watershed

Abstract: Microbial contamination of recreation waters is a major concern globally, with pollutants originating from many sources, including human and other animal wastes often introduced during storm events. Fecal contamination is traditionally monitored by employing culture methods targeting fecal indicator bacteria (FIB), namely E. coli and enterococci, which provides only limited information of a few microbial taxa and no information on their sources. Host-associated qPCR and metagenomic DNA sequencing are complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…Metagenomic sequencing has been used to explore AMR trends in anthropogenically impacted environments ( 41 ) and to detect wastewater associated enteric pathogens ( 36 , 95 ). However, viability or infectious potential of detected microorganisms requires additional analysis of metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metagenomic sequencing has been used to explore AMR trends in anthropogenically impacted environments ( 41 ) and to detect wastewater associated enteric pathogens ( 36 , 95 ). However, viability or infectious potential of detected microorganisms requires additional analysis of metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of wastewater associated pathogens by employing molecular techniques has been done at WWTPs ( 36 , 38 , 124 ) and used for source tracking of fecal pollution ( 126 , 95 , 54 ). However, a major hurdle for WS is communication of the results and their interpretation to public health officials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA metagenome sequencing (metagenomics) is a valuable technology for detection of all Vibrio spp. in the environment, including VBNC Vibrio, and is particularly useful because it simultaneously profiles virulence and antimicrobial resistance associated genes (Roy et al, 2018;Acharya et al, 2020;Brumfield et al, 2020Brumfield et al, , 2021. Most of the HTS studies reported to date have focused on clinical isolates obtained by culture previously from patient samples.…”
Section: Molecular Methods For Detection and Genomic Analysis Of Vibrio Sppmentioning
confidence: 99%
“…Intense rainfall will not only alter the salinity profile but also nutrient availability in coastal rivers, with increasing inflow of freshwater. Stormwater runoff can also promote transmission of antimicrobial resistance and virulence associated genes among bacteria (Brumfield et al ., 2021). The evidence is clear that Vibrio spp .…”
Section: Impact Of Climate and Environment On Diseases Caused By Vibr...mentioning
confidence: 99%